Simple Ultrasound Imaging System Based on Dense and Sparse Selection and Activation of Array Transducer Elements - Mohammad Syaryadhi; Eiko Nakazawa; Norio Tagawa (IEEE Access, 2025)
Ultrasound imaging is typically performed using an array transducer system. To obtain a direct 3D image instead of stacking 2D cross-sectional images, a 2D array is required, which requires a large amount of electronic circuitry. Therefore, simple single transducer systems are being investigated. However, these single-transducer systems require multiple echo receptions by rotating or translating the transducer to achieve sufficient image quality, making them difficult to apply to specific imaging targets. In this study, we propose a method that selectively connects multiple elements instead of using all elements of the array to receive independently, aiming to reduce the size of the receiving electronic circuitry. By selecting and connecting elements in dense and sparse patterns, we have developed a method that considers both resolution and signal-to-noise ratio. Through phantom experiments and human in vivo imaging experiments, it has been demonstrated that the proposed method achieves image quality equivalent to that of conventional array transducers.